Pengaruh Teknik Preview, Question, Read, Summarize, Test (PQRST) Dan Kemampuan Literasi Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Kurikulum Pembelajaran - Bekata, Halena M.; Y. Daik, Triznawasti; Fanpada, Nehemia; Mata, Yessy; Oualeng, Adolfina (Peneliti.net, 2025)
This study aims to determine the influence of the use of the Preview, Questions, Read, Summarize, Test (PQRST) reading method and reading literacy skills on student learning outcomes in the learning curriculum course. The method used in this study is a quantitative method with a causal associative approach that is used to find out the causal relationship. The design used in this study uses a dual paradigm with two independent variables X1 and X2 and one dependent vaiabel Y. The population in this study is students of the Teacher Education Study Program, Elementary School, Faculty of Teacher Training and Education, Tribuana Kalabahi University. The sample used in this study uses a simple random sampling type probability sampling technique. The data collection techniques used are tests, questionnaires and observations. The data analysis technique used is descriptive and inferential statistics with a double linear regression formula. The results showed that the influence of PQRST techniques was greater by 87.16% and literacy ability by 67.4% on student learning outcomes by 81.7%. This means that the PQRST method has a greater influence on student learning outcomes. Thus, it can be concluded that the use of the PQRST method in learning accompanied by reading literacy skills from students can improve reading literacy skills and student learning outcomes in learning curriculum courses.